Desempenho ao exercício e qualidade de vida em pacientes com sobreposição da DPOC e insuficiência cardíaca com e sem força muscular preservada - Oliveira, Ligia Biazzim de [UNIFESP] (2018)
Patients with chronic obstructive pulmonary disease and heart failure have exercise intolerance and poorer quality of life when compared to those with isolated diseases. It has been observed that the reduction of inspiratory muscle strength influences the aforementioned outcomes. Objective: To compare exercise tolerance and quality of life in patients with chronic obstructive pulmonary disease and associated heart failure who have or are not affected by inspiratory muscle strength. METHODS: Eighteen patients with associated chronic obstructive pulmonary disease and heart failure (GOLD II-III and left ventricular ejection fraction <50%) were randomly assigned to two groups: 8 patients with maximal inspiratory pressure ≤70 cmH2O and 10 patients with maximum inspiratory pressure> 70 cmH2O. All patients underwent the six-minute walk test, incremental cardiopulmonary exercise test on cycle ergometer, and quality of life measures. Results: Despite similar mean values in the exams: post bronchodilator spirometry (FEV1: 62 ± 16 versus 55 ± 0.9% predicted (p 0.40), FEV1 / FVC: 70 ± 12% versus 76 ± 13 (p 0.30)) and ejection fraction (41 ± 4 versus 38 ± 4% (p 0.10), patients with greater inspiratory muscle strength impairment had a shorter distance walked in the six-minute walk test (316 ± 16 versus 460 ± 12 meters (p <0.01)), lower V̇O2 (p <0.05) and worse quality of life assessed by questionnaires: Saint George (scores in the impact domain: 21 ± 15 versus 8 ± 6 (p <0.01) and in the symptom domain: 46 ± 30 versus 23 ± 14 (p 0.05)) and by the Minnesota questionnaire (9 ± 6 versus 24 ± 12 (p <0.01).) Conclusion: Patients with chronic obstructive pulmonary disease associated with heart failure muscle that have lower inspiratory muscle strength have worse tolerance to exercise and quality of life when compared to patients with greater inspiratory muscle strength.